Notes for a debate on technology and musical education - Calazans, Marcelo Vizani; Carreira Ricon, Leandro Couto (Revista Hipótese, 2022)
This theoretical reflection article originated from a master's research at the University of Lisbon. From the review of available specialized literature, the article seeks to analyze the relationship between music education and the use of new information and communication technologies. For this, starting from authors such as Amato (2018), Bauer (2014), Chamorro (2017), and Iazzetta (2009), we seek to situate the phenomenon of technology in education to then signal the use of technology specifically in music education, problematizing teacher training in music education and the use of technologies.
Keywords: Music education; Teacher formation; Information and communication technology